2015
DOI: 10.14720/aas.2015.105.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effect of medicinal plant Cannabis sativa L. on Lactuca sativa L. seed germination

Abstract: In order to examine allelopathic effect of Cannabis sativa L. on germination capability and seedling growth of Lactuca sativa L., a study was performed in laboratory conditions. Treatments were set up in randomised block design in four replications for each of four concentration ranges of 25, 50, 75 and 100 % of aqueous extract made of shoot parts and 4 identical extract concentrations made of root of cannabis. Control variant was lettuce seed treated by distilled water. During the studies shoot and seminal ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…These results match with those observed in previous studies showing that increased temperature stimulates the production of higher allelochemical concentrations, which could have stronger effects on acceptor species (Wang et al 2011, Zhang et al 2014. However, our results indicated a different response of the root and shoot extracts of dominant species to seed germination at all temperatures compared with the data obtained in previous studies (Mahmoodzadeh et al 2015, Gulzar & Siddiqui 2014. A weaker inhibition of root extracts has been specified for other plant species, for example Heracleum mantegazzianum (Apiaceae -Balezentiene & Renćo 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results match with those observed in previous studies showing that increased temperature stimulates the production of higher allelochemical concentrations, which could have stronger effects on acceptor species (Wang et al 2011, Zhang et al 2014. However, our results indicated a different response of the root and shoot extracts of dominant species to seed germination at all temperatures compared with the data obtained in previous studies (Mahmoodzadeh et al 2015, Gulzar & Siddiqui 2014. A weaker inhibition of root extracts has been specified for other plant species, for example Heracleum mantegazzianum (Apiaceae -Balezentiene & Renćo 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The different allelopathic effects of the shoots and roots of dominant species has also been documented by other authors (Gulzar & Siddiqui 2014). Mahmoodzadeh et al (2015) noted that the different qualitative composition and quantitative content of biologically active compounds might explain the different effects of shoots and roots of dominant species. Moreover, the inhibitory effect of extracts from different parts of plant dominants on seed germination at all temperatures might be due to imbalance in metabolism regulated by various enzyme activities (Oyun 2006).…”
Section: Discussionsupporting
confidence: 55%
“…The second assay measures the survival of brine shrimp (Artemia salina) cysts after challenging with extracts. The complete description of each test is reported in previous papers [25,26].…”
Section: Eco-toxicological Assaysmentioning
confidence: 99%
“…It is also reported that the chemicals of different part of the same plant can showed phytotoxic, inhibitory or stimulatory effects on other recipient plants. Mehmoodzadeh et al [25] reported the allelopathic effect of Cannabis sativa shoot and root extract where shoot showed inhibitory effects while root gave stimulatory effects on seeds of Lactuca sativa. Present study showed that at 20mg radicle length of Lactuca sativa was least with Monotheca buxifolia (0.12), followed by Cucumis sativus (0.14) and Malus baccata (0.63).…”
Section: Resultsmentioning
confidence: 99%